2020
DOI: 10.1111/odi.13343
|View full text |Cite
|
Sign up to set email alerts
|

Topical pilocarpine for xerostomia in patients with head and neck cancer treated with radiotherapy

Abstract: ObjectiveTo evaluate a pilocarpine spray as a treatment for xerostomia in patients treated with radiotherapy (RT) for head and neck cancer (HNC).MethodsThis was a placebo‐controlled, double‐blind, crossover clinical trial of patients complaining of dry mouth after RT for HNC. Forty patients were randomly assigned to either placebo or pilocarpine (1.54%) spray and instructed to use three times a day for 3 months. After 1‐month washout period, patients were crossed over to receive placebo or pilocarpine. The ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
17
2
1
Order By: Relevance
“…In addition, when the effectiveness of a pilocarpine spray as a treatment for xerostomia through a prospective, randomized, double-blind, crossover, placebo-controlled clinical trial was examined by the research team of Santos Polvora [87], the salivary flow of the pilocarpine-treated participants was significantly increased after the utilization of the spray. Yet, it is worth mentioning that these results are in disagreement with the findings of the study carried out by Pereira et al [88], according to which the performance of the evaluated pilocarpine spray was similar to that of the placebo on the patient's stimulated whole saliva flow. In this specific study, 40 patients suffering from radiation-induced xerostomia were randomly assigned to either the placebo or pilocarpine spray group.…”
Section: Topical Administration Of Pilocarpinecontrasting
confidence: 92%
“…In addition, when the effectiveness of a pilocarpine spray as a treatment for xerostomia through a prospective, randomized, double-blind, crossover, placebo-controlled clinical trial was examined by the research team of Santos Polvora [87], the salivary flow of the pilocarpine-treated participants was significantly increased after the utilization of the spray. Yet, it is worth mentioning that these results are in disagreement with the findings of the study carried out by Pereira et al [88], according to which the performance of the evaluated pilocarpine spray was similar to that of the placebo on the patient's stimulated whole saliva flow. In this specific study, 40 patients suffering from radiation-induced xerostomia were randomly assigned to either the placebo or pilocarpine spray group.…”
Section: Topical Administration Of Pilocarpinecontrasting
confidence: 92%
“…Previously, a clinical trial using a spray formulation of 1.54% pilocarpine solution for xerostomia (XI) showed no statistical difference in stimulated salivary flow rates between pilocarpine and placebo ( 20 ). However, another study demonstrated improvement following the use of topical pilocarpine in moisture sensation and other subjective parameters ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Topical pilocarpine may be considered as an alternative to minimize the side effects of systemic administration. Previous studies have been performed on the effectiveness of topical pilocarpine as a mouthwash, Tablets, lozenge, spray ( 16 - 20 ), however, the study of topical applications of pilocarpine combined with artificial saliva has not been reported. It is hypothesized that combining topical pilocarpine as an active ingredient with artificial saliva should alleviate xerostomia.…”
Section: Introductionmentioning
confidence: 99%
“…Most had a medium to high risk of bias. Among the 13 randomized studies, there were 12 with a medium 13,14,16,18,20 to high 12,15,17,19,[21][22][23] risk of bias, and only one study with a low 24 risk of bias.…”
Section: Quality Of the Evidencementioning
confidence: 99%